Penentuan Jalur Truk Sampah Menggunakan Algoritma A* Dan Skor Kepadatan Penduduk - Eka Himawanto; Kiki Maulana Adhinugraha; Ibnu Asror (eProceedings of Engineering, 2017)
The high growth of urban population and the increasing of development activities in various sectors caused various problems in urban areas such as slums and garbage. Based on data from the Settlement and Spatial Office of Tegal City, in 2015 there are about 600 m3 of Garbage per day transported from TPST to TPA. In the process of transporting garbage only focuses on finding the shortest path but do not pay attention to the comfort of the residents who are in one of the garbage truck routes. The purpose of this research is to search the shortest path and avoid path that have too many civilian activity from a TPST track to TPA Mataram, Tegal City . A* algorithm is used to search the shortest path and avoid path that have too many civilian activity of garbage truck in Tegal City.The calculation begins by creating a network graph of garbage transport first. TPST, TPA and intersection as nodes and roads connect between nodes as edge. After the network is formed, then the matrix is based on the population density of each neighboring node on the network and performs the calculation process using the A * algorithm to obtain the path matrix value with the corresponding population density between each optimum point. Implementation of this algorithm is done in Tegal City because there is no exact route in the process of transporting garbage from TPST to TPA. The A * algorithm is used in this case because in the process of tracking algorithm A * using heuristic value, so that in route selection can be produced an accurate route. In this case the result to be achieved is the optimum route by minimizing through the crowded lanes Keywords: A*, node, path, TPST, TPA, intersection ,garbage transport, population density.